(untitled) (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Basic Sciences Series, 2026)
A detailed facies investigation was carried out to examine the Lower and Middle Jurassic deposits in the Bab Janna and Al‑Sha‘rah sections within the Al‑Haffeh area. The study involved petrographic analysis of hard‑rock thin sections and the extraction of fossil assemblages from soft samples to evaluate depositional energy and infer the sedimentary environment. Facies classification was conducted using the Wilson (1975) scheme to ensure accurate identification. The results show a clear dominance of the Bioclastic wachstone face, which appears repeatedly throughout the sections, whereas the SMF_8(whole shells in micrite) occurs less frequently. A notable abundance of benthic organisms was recorded without the appearance of new taxa of additional chronostratigraphic significance. Fossils characteristic of the Lower and Middle Jurassic, including Thaumatoporella parvovesiculifera and Kurnubia palastiniensis, were documented, confirming a Callovian age. The facies evidence further indicates a relatively stable sea‑level regime and a shallow, warm open‑shelf setting that favored the deposition of micrite and clay. The presence of calcareous algae and sponge spicules reflects normal salinity and low‑energy conditions, while partial dolomitization of some layers suggests limited local shifts toward a tidal environment before the system returned to relative stability.